2023
DOI: 10.1177/07316844231173059
|View full text |Cite
|
Sign up to set email alerts
|

Improving surface smoothness in FDM parts through ironing post-processing

Abstract: Additive manufacturing using fused deposition modelling (FDM) is an affordable and efficient way to produce functional parts and prototypes. However, the FDM-manufactured parts, particularly those made of polylactic acid (PLA), has some drawbacks regarding accuracy and surface finish. To address this, post-processing techniques such as ironing can be applied. However, little is known about the effect of ironing process parameters on surface roughness, and there is a lack of comparative studies on contact and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Alzyod et al . investigated the effect of path speed, ironing spacing and flow rate on the surface quality of PLA samples fabricated with FDM using contact and non-contact measurement methods (Alzyod et al. , 2023).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alzyod et al . investigated the effect of path speed, ironing spacing and flow rate on the surface quality of PLA samples fabricated with FDM using contact and non-contact measurement methods (Alzyod et al. , 2023).…”
Section: Resultsmentioning
confidence: 99%
“…In another study, they observed that PLA had better surface quality than ABS material. Alzyod et al investigated the effect of path speed, ironing spacing and flow rate on the surface quality of PLA samples fabricated with FDM using contact and non-contact measurement methods (Alzyod et al, 2023). The results demonstrated that the ironing process can lead to an important reduction in surface roughness values, and careful optimization of process parameters can further minimize roughness.…”
Section: Discussionmentioning
confidence: 99%
“…PLA (Polylactic Acid) is a commonly chosen material for numerous 3D printing applications due to its excellent dimensional stability, minimal shrinkage, and ease of printing. PLA is a thermoplastic derived from renewable resources and is recognized for its ability to produce high-quality prints with a smooth surface finish (Alzyod et al, 2023;Fekete et al, 2021;). While the properties of PLA can vary depending on the specific manufacturer, the ranges provided in Table 1 offer a good understanding of the material's general characteristics.…”
Section: D Printer Materials and Printing Methodsmentioning
confidence: 99%
“…However, in this study, we aim to study the effect of using the ironing post-processing technique after every printed layer on the mechanical properties of PLA components made utilizing the MEX process. Ironing has shown promising results in improving surface quality by reducing surface roughness and decreasing the visibility of layer lines [34]. By performing ironing as a processing step, the aim is to improve the adhesion between layers and enhance the mechanical properties of the part by reducing the occurrence of interlayer voids and delamination.…”
Section: Introductionmentioning
confidence: 99%